Aeration at overflow dams with curved surfaces by different flashboard spillways - Chu, Kejian; Hua, Zulin; Ji, Lijun (Journal of Environmental Engineering and Landscape Management, 2014)
Aeration using overflow dams is an eco-friendly and economical method of improving dissolved oxygen levels in polluted urban streams. Laboratory investigations of aeration performance in smooth spillways, as well as in parallel flashboard and interlaced flashboard spillways with different flashboard intervals, for overflow dams with curved surfaces have been conducted separately. Aeration efficiencies of the different types of spillways, in particular the effects of varying discharge rate, total spillway height, and flashboard interval, have been discussed in detail. The test data illustrate that aeration efficiency in all spillways increases with spillway height and decreases with increasing discharge. Flashboard spillways appear to provide significantly higher aeration efficiency than smooth ones, and aeration efficiency increases with the number of flashboards, but with a continuously declining growth rate. By combining Fds with hd*, a new dimensionless parameter Ψ is created to characterize the comprehensive effects of hydraulic conditions on aeration. Empirical formulas for oxygen-transfer efficiency in smooth, parallel flashboard, and interlaced flashboard spillways have been developed with Ψ and the dimensionless number of flashboards per unit area of spillway N* as independent variables, and the properties of these formulas are discussed.First published online: 11 Aug 2014